Decreased plasma levels of PDGF-BB, VEGF-A, and HIF-2α in preterm infants after ibuprofen treatment - Huang, Xuemei; Han, Dongshan; Wei, Yanfei; Lin, Bingchun; Zeng, Dingyuan; Zhang, Yu; Wei, Ba; Huang, Zhifeng; Chen, Xueyu; Yang, Chuanzhong (Frontiers in Pediatrics, 2022)
Introduction Ibuprofen is one of the most common non-steroidal anti-inflammatory drugs used to close patent ductus arteriosus (PDA) in preterm infants. PDA is associated with bronchopulmonary dysplasia (BPD), while PDA closure by ibuprofen did not reduce the incidence of BPD or death. Previous studies have indicated an anti-angiogenesis effect of ibuprofen. This study investigated the change of angiogenic factors after ibuprofen treatment in preterm infants. Methods Preterm infants with hemodynamically significant PDA (hsPDA) were included. After confirmed hsPDA by color doppler ultrasonography within one week after birth, infants received oral ibuprofen for three continuous days. Paired plasma before and after the ibuprofen treatment was collected and measured by ELISA to determine the concentrations of platelet-derived growth factor-BB (PDGF-BB) and vascular endothelial growth factor A (VEGF-A), and hypoxia-inducible factor-2α (HIF-2α). Results 17 paired plasma from infants with hsPDA were collected. The concentration of PDGF-BB and VEGF-A significantly decreased after ibuprofen treatment (2034 vs. 986 pg/mL for PDGF-BB, 628 vs. 298 pg/mL for VEGF-A). HIF-2α level showed a tendency to decrease after ibuprofen treatment, although the reduction was not statistically significant (p=0.077). Conclusion This study demonstrated decreased vascular growth factors after ibuprofen exposure in hsPDA infants.